SEJARAH KEHIDUPAN MASYARAKAT SUKU BONAI DESA BABUSSALAM ROKAN KECAMATAN PUJUD KABUPATEN ROKAN HILIR - Putri, Guswita; Isjoni, Isjoni; Melay, Ridwan (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Bonai tribe is one of the isolated tribes in Riau that lives on the banks of the Rokan River. This Bonai tribe spreads in several regions such as Left Rokan and Rokan Kanan. The Bonai Tribe is one of the KAT communities in Riau which is a marginal community that is marginalized in all aspects of its life. The KAT community in Indonesia is spatially or geographically located far from the centers of progress and development that exist. A community becomes alienated due to several factors including geographical distance, social interaction, science and technology, education. According to the Bonai Tribe, the word